School-Based Prevention of Problem Behaviors: A Meta-Analysis - Wilson, David B. (Journal of quantitative criminology, 2001)
This study examines the features of effective school-based prevention of crime, substance use, dropout/nonattendance, and other conduct problems. It summarizes, using meta-analytic techniques, results from 165 studies of school-based prevention activities that ranged from individual counseling or behavior modification programs through efforts to change the way schools are managed. The results highlight several inadequacies in the existing research for guiding policy and practice, the most notable of which is that many popular school-based prevention approaches have not been well studied to date. The study shows, however, that school-based prevention practices appear to be effective in reducing alcohol and drug use, dropout and nonattendance, and other conduct problems. The size of the average effect for each of the four outcomes was small and there was considerable heterogeneity across studies in the magnitude of effects, even within program type after adjusting for measured method and population differences. Non-cognitive-behavioral counseling, social work, and other therapeutic interventions show consistently negative effects, whereas self-control or social competency promotion instruction that makes use of cognitive-behavioral and behavioral instructional methods show consistently positive effects. Also effective are noninstructional cognitive-behavioral and behavioral methods programs. Environmentally focused interventions appear to be particularly effective for reducing delinquency and drug use.